Uji Aktivitas Antioksidan Ekstrak Buah Kersen (Muntingia calabura L.) Menggunakan 1,1-Difenil-2-Pikrilhidrazil - Zela Zela; Anang Wahid Muhammad Diah (Media Eksakta, 2021)
Kersen, also known as Muntingia calabura L. is a fruit with numerous health benefits that can be ingested instead of medication. The goal of this study was to see how effective the extract Muntingia calabura L. was as an antioxidant. This study used DPPH (2,2-diphenyl-1-picrylhydrazyl) as a source of free radicals and vitamin C as a positive control to measure antioxidant activity. A UV-VIS spectrophotometer was used to determine the antioxidant activity of Muntingia calabura L. extract. The fruit powder of Muntingia calabura L. was extracted using the maceration process using ethanol as a solvent. The antioxidant activity of the extract was next examined at various concnetration of 20, 40, 60, and 80 ppm. Muntingia calabura L. extract had a strong antioxidant power with an IC50 value of 69.662 ppm, while vitamin C had also a strong antioxidant power with an IC50 value of 79.615 ppm, according to the findings. Muntingia calabura L. fruit extract is a good source of natural antioxidants, according to the IC50 value, because it has a high antioxidant activity value.